2010
DOI: 10.2214/ajr.09.3287
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pain After Percutaneous Vertebroplasty

Abstract: Percutaneous vertebroplasty is widely used to treat patients with symptomatic osteoporotic compression fractures. Although the procedure relieves the pain of the compression fracture, recurrent back pain after percutaneous vertebroplasty is common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
1
28
0
1
Order By: Relevance
“…PVP appeared to relieve pain effectively and restore vertebral body height in most studies [3, 21]. Although PVP relieves the pain of compression fractures, recurrent back pain after PVP is common [21]. Among our group B patients, the VAS score was 2.95 ± 1.56 at month 12 and 3.14 ± 1.58 at month 18 ( p  = 0.329).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…PVP appeared to relieve pain effectively and restore vertebral body height in most studies [3, 21]. Although PVP relieves the pain of compression fractures, recurrent back pain after PVP is common [21]. Among our group B patients, the VAS score was 2.95 ± 1.56 at month 12 and 3.14 ± 1.58 at month 18 ( p  = 0.329).…”
Section: Discussionmentioning
confidence: 83%
“…Kallmes et al demonstrated in a randomized controlled trial that improvements in pain and pain-related disability associated with osteoporotic VCFs in patients treated with vertebroplasty were similar to the improvements in a simulated procedure without the use of cement (control group) [20]. PVP appeared to relieve pain effectively and restore vertebral body height in most studies [3, 21]. Although PVP relieves the pain of compression fractures, recurrent back pain after PVP is common [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, pain can recur in 1.8-15.6% of patients after VP, which is attributable to rib fracture, infection, non-healing bone-cement interface, or new symptomatic compression fractures [7]. In addition, inadequate impactions of bone cement can make the unfilled intravertebral spaces collapse or the injectates loosen after procedures [6].…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms exist for pain after vertebral augmentation procedures. Same/adjacent level pain may result from vertebral body deformity at the fracture site, cement leakage, fracture progression, a new VCF, facet arthropathy, nerve root entrapment, rib fractures, infection, and non-healing bone-cement interface [5]. In the presence of high-grade pain during the immediate/subacute post-procedure period, specific causes related to the fracture and/or procedure must be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The facet joints, both at same/adjacent levels and non-adjacent levels, as well as an L4 spinal nerve, were responsible for the other types of pain. Non-adjacent level pain may result from pre-existing lumbar spine pathology, including lumbar spinal stenosis, spondylosis, spondylolisthesis, and facet arthropathy [5]. Multiple axial structures may contribute to patients’ pain including intervertebral discs, muscles, ligaments, nerves, and fascia.…”
Section: Discussionmentioning
confidence: 99%